PSEUDO ABSTRAKSI REFLEKTIF DALAM MENYELESAIKAN MASALAH BARISAN BILANGAN - Surya Sari Faradiba; Anies Fuady; Desy Nofita Sari (STKIP Andi Matappa, 2020)
This research is a descriptive study. The research objective was to describe the reflective abstraction process experienced by students. The research subject was a class VIII student. The sampling technique used was purposive sampling. The subjects were chosen because they considered their communication skills which were quite good compared to their peers, making it easier for researchers to explore data. In addition, the selected subjects were students with very satisfying academic achievements compared to their classmates. This study examines and explains the reflective abstraction that the subject does in solving the number sequence problem. The focus of research is the process of reflective abstraction which includes interiorization, coordination, reversal, encapsulation, and generalization. The results showed that the reflective abstraction stage did not guarantee arriving at the correct solution. In this study the subject performs all stages of reflective abstraction starting from interiorization, coordination, reversal, encapsulation, and generalization, but the final solution is wrong. This phenomenon is said to be pseudo-reflective abstraction or pseudo-reflective abstraction.